Sazonalidade, tarifa mais conveniente e fator de carga em indústria de processamento de cana - De Souza, Luiz Gonzaga [UNESP] (My University, 1997)
This paper represents the results of the work carried out in order to study the condition of seasonal consumer, the load factor and the more convenient tariff for a sugar mill located in the Vale do Paranapanema, SP, Brazil. Therefore, data of consume and registered demand were collected during the quadriennium 1990 to 1994. The studies showed that the factory did not maintain the condition of seasonal consumer of electric energy during the analysed period. Low values of the load factor observed in the period showed a non rational use of electric energy supplied by the concessionary. The results showed that only in one situation (load retired in top equal to 90%) the most convenient tariff is the horo-sazonal azul. In the other situations the most convenient tariff is the conventional one.

O presente trabalho teve por objetivo avaliar as condições de sazonalidade, a racionalização no uso da energia elétrica e a tarifa mais conveniente para uma indústria de processamento de cana localizada no Vale do Paranapanema, SP. Para tanto, foram coletados, na indústria, dados de consumo e de demanda registrada de 4 safras: 1990/91, 1991/92, 1992/93 e 1993/94. A análise dos dados mostra que a usina não conseguiu manter, no período, a condição de consumidor sazonal. Os baixos valores do fator de carga observados indicam o uso não-racional da energia elétrica adquirida. Os resultados obtidos revelam que apenas na situação de carga retirada na ponta igual a 90% a tarifa mais conveniente é a horo-sazonal azul; nas demais situações, a tarifa mais conveniente, isto é, a de menor importância para a usina, é a convencional.
Seasonality, more convenient tariff and load factor on a sugar cane factory
Keywords: Electric parameters; Seasonal consumer; Sugar mill